Evaluación preliminar del riesgo sanitario por agroquímicos en aguas del arroyo Azul, provincia de Buenos Aires - Peluso, Fabio O. (2008)
Health risk analyses (HRA) indicate whether, and to which extent of severity, a given chemical substance may constitute a threat for health, e.g., the accidental ingestion of water during recreational use with direct contact. Objectives of this paper are to estimate the risk from an accidental ingestion of water carrying agrichemicals (á y ä HCH, Aldrine, ã – Chlordane, Glyphosate, and Imazethapyr) while bathing in the Azul River bathing resort by making use of HRA, and to discuss the potential use of such a tool for water resources management. It is based on the USEPA model, and, with the exception of the concentration of the substance in water, all other variables (ingestion rate, weight of individuals, frequency and duration of the exposition) are treated probabilistically and fit a recreational scenario with direct contact. The aggregated risk is estimated with an additive model of the particular risk of each substance. Results show that the risk, non carcinogenetic effects, may be disregarded because its value is always less than 1 (Aldrine is the principal contributor). Regarding the carcinogenetic effects, although the value is slightly greater than the limiting value of 10-5, the conservative approach of this study makes it to be minimized (its principal contributor is á –HCH). The Buenos Aires Province does not count with regulations referred to the quality of natural waters used for bathing. For that reason, the HRA stand out as an option for decision-makers given the absence of alternative management strategies.